Dampak perkembangan keterampilan makan yang tidak baik pada anak - Grace Riris Vintany Siahaan; Tiangsa Sembiring; Tri Faranita; Winra Pratita (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Feeding skills are complex process that involves development of sensoric and motoric abilities. Feeding skills are influenced by anatomical, neurophysiological, and socio-cultural environment. Introduction of proper food that accordance with development of oromotor skills result in perfect development of feeding skill and also reinforce bonding between mother and child. Inappropiate feeding skills development will adverse bad impact on nutritional status, psychological development and the onset of feeding difficulties.Keywords : feeding skil; children